MICROFOCUSED ULTRASOUND FOR FACE LIFT: CASE SERIES - Mendonça de Oliveira, Larissa; Regina Veronezi, Lauscea; Vivianne Nogueira, Marcia; Rabelo Lima Barbosa, Chrystianne; Rodrigues Ribeiro, Henrique; Lemos Maia, Juliana; Elayne Silva Montezuma, Gina; Januzzi Santos, Marcelo (Health and Society, 2023)
The evolution of technology in aesthetics and the concern to carry out less invasive procedures has given more and more space to procedures such as microfocused ultrasound. In this context, the main objective of this study was to evaluate the clinical efficacy of microfocused ultrasound for a facelift and its durability after months of application. Materials and methods: The procedure was carried out on 5 patients (N=5) in the middle/lower third of the face, and followed up for 4 months (120 days). Digital images of each subject were taken before and after treatment with the Vectra H2 system and after 4 months of the protocol. A questionnaire was administered among the patients involved in the study about their level of satisfaction with the procedure and among dental professionals who were not involved in the study, according to the GAIS scale. Results: A facelift was observed after 4 months in 100% of the cases and increased in 60% of the patients in the study. The majority of patients rated their satisfaction with the outcome of the treatment between number 2-(Improved a lot) (40%) and number 1-(Improved a lot) (40%). Around 20% rated their satisfaction with the procedure as number 3-(Improved), while in the blinded observers’ assessment, 80% rated the result as number 2-(Improved a lot) and 20% as number 1-(Improved a lot). There were no ratings of 4-(No improvement at all) or 5-(Worsened). Conclusion: The facelift obtained through microfocused ultrasound was maintained for four months after the procedure in all patients, when compared to stage 0 (before the protocol).